Amelioration of saline–sodic soil with gypsum can increase yield and nitrogen use efficiency in rice–wheat cropping system. Issue 9 (29th July 2017) - Murtaza, Behzad; Murtaza, Ghulam; Sabir, Muhammad; Owens, Gary; Abbas, Ghulam; Imran, Muhammad; Shah, Ghulam Mustafa
ABSTRACT: A 2-year field experiment was conducted to determine crop yield and N use efficiency (NUE) from a saline–sodic soil (clay loam) with and without application of gypsum. Treatments included two N application rates (15% and 30%) higher than the recommended one to the normal soil, and gypsum added at 50% and 100% of soil gypsum requirement (SGR) to the saline–sodic soil, both cultivated with rice and wheat during 2011–2013. Results revealed a decrease in pH of saturated soil paste (pHs ), electrical conductivity of saturation extract (ECe ), sodium adsorption ratio (SAR) and exchangeable sodium percentage with N fertilizer along with gypsum application in saline–sodic soil. However, the effect was most prominent when gypsum was added at 50% of SGR. Crop yield and NUE remained significantly lower ( p < 0.05) in saline–sodic-soils as compared to normal soil. However, gypsum application reduced this difference from 47% to 17% since both yield and NUE increased considerably. Crop yield and NUE remained higher for wheat than for rice. During first year, higher doses of N with gypsum application at 50% SGR proved most effective, whereas, in subsequent year, recommended N along with gypsum at 50% SGR became more profitable. All these results lead us to conclude that gypsum application can ameliorate saline–sodic soil thereby increasing crop yield and NUE.